2020
DOI: 10.1007/s10096-020-03925-5
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus capitis isolated from bloodstream infections: a nationwide 3-month survey in 38 neonatal intensive care units

Abstract: To increase the knowledge about S. capitis in the neonatal setting, we conducted a nationwide 3-month survey in 38 neonatal intensive care units (NICUs) covering 56.6% of French NICU beds. We demonstrated 14.2% of S. capitis BSI (S.capBSI) among nosocomial BSIs. S.capBSI incidence rate was 0.59 per 1000 patient-days. A total of 55.0% of the S.capBSIs were late onset catheter-related BSIs. The S. capitis strains infected preterm babies (median gestational age 26 weeks, median birth weight 855 g). They were resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Previous reports demonstrated that S. epidermidis and S. capitis were detected in the GI tract and from aerosols after dental procedures 19–21 . S. capitis , mostly detected in CS, is a sepsis causative microorganism that occurs due to bacterial translocation from the intestine, 22 causing severe infections, especially in children susceptible to infection. Furthermore, 16S rRNA gene sequencing in DE without WCP identified Micrococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that S. epidermidis and S. capitis were detected in the GI tract and from aerosols after dental procedures 19–21 . S. capitis , mostly detected in CS, is a sepsis causative microorganism that occurs due to bacterial translocation from the intestine, 22 causing severe infections, especially in children susceptible to infection. Furthermore, 16S rRNA gene sequencing in DE without WCP identified Micrococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The most common presentation for S. capitis infection in neonates was bacteraemia, with or without the presence of a central venous catheter (CVC) [ 81 ]. In one CoNS bacteraemia study, 50% of cases were catheter-related, and 67.1% of these were linked to CVCs, while other sources included the digestive tract (12.1%) and skin (8.5%) [ 82 ]. In a 2020 study by Adeghate et al [ 83 ], it was noted that gastrointestinal tract colonisation with CoNS was associated with an increased incidence of bacteraemia, with both CoNS and Enterobacterales species [ 83 ].…”
Section: Staphylococcus Capitis Infection and Colonisation I...mentioning
confidence: 99%
“…However, no adult outbreaks have been reported in the peer-reviewed literature [ 91 ]. Most centres in France still routinely use vancomycin to treat bacteraemia, even in the presence of an NRCS-A clone outbreak, as the isolates are phenotypically sensitive to vancomycin, although they are resistant to gentamicin and methicillin [ 82 ].…”
Section: Neonatal Outbreaksmentioning
confidence: 99%
“…Recently, isolates have emerged that are also resistant to vancomycin [21]. The NRCS-A clone of S. capitis has emerged as a pathogen within NICUs worldwide, and many isolates show some degree of vancomycin resistance [22,23]. Identification of methicillinresistant S. aureus strains that are also vancomycinintermediate or vancomycin-resistant is similarly concerning.…”
Section: Gram-positivementioning
confidence: 99%